Eric Rohmer - Tester, K. author. aut Link
VI, 175 p.
Keywords: Since the 1950s Eric Rohmer has been one of the major presences in French cinema as critic and director. This book is a sophisticated engagement with his work in which Keith Tester argues that Rohmer is not the naIve realist he is often claimed to be. Instead, his films are revealed as a sustained exercise in Catholic theology.